Deletion of connective tissue growth factor ameliorates peritoneal fibrosis by inhibiting angiogenesis and inflammation. Issue 6 (17th November 2017) - Toda, Naohiro; Mori, Kiyoshi; Kasahara, Masato; Koga, Kenichi; Ishii, Akira; Mori, Keita P; Osaki, Keisuke; Mukoyama, Masashi; Yanagita, Motoko; Yokoi, Hideki
ABSTRACT: Background: Connective tissue growth factor (CTGF/CCN2) regulates the signalling of other growth factors and promotes fibrosis. CTGF is increased in mice and humans with peritoneal fibrosis. Inhibition of CTGF has not been examined as a potential therapeutic target for peritoneal fibrosis because systemic CTGF knockout mice die at the perinatal stage. Methods: To study the role of CTGF in peritoneal fibrosis of adult mice, we generated CTGF conditional knockout (cKO) mice by crossing CTGF floxed mice with RosaCreER T2 mice. We administered tamoxifen to Rosa-CTGF cKO mice to delete the CTGF gene throughout the body. We induced peritoneal fibrosis by intraperitoneal injection of chlorhexidine gluconate (CG) in wild-type and Rosa-CTGF cKO mice. Results: Induction of peritoneal fibrosis in wild-type mice increased CTGF expression and produced severe thickening of the peritoneum. In contrast, CG-treated Rosa-CTGF cKO mice exhibited reduced thickening of the peritoneum. Peritoneal equilibration test revealed that the excessive peritoneal small-solute transport in CG-treated wild-type mice was normalized by CTGF deletion. CG-treated Rosa-CTGF cKO mice exhibited a reduced number of αSMA-, Ki67-, CD31- and MAC-2-positive cells in the peritoneum. Analyses of peritoneal mRNA showed that CG-treated Rosa-CTGF cKO mice exhibited reduced expression of Cd68, Acta2 (αSMA), Pecam1 (CD31) and Vegfa . Conclusions: These results indicate that a deficiency of CTGF can reduce peritoneal thickening and help to maintain peritoneal function by reducing angiogenesis and inflammation in peritoneal fibrosis. These results suggest that CTGF plays an important role in the progression of peritoneal fibrosis.